Samosa Kulit Buah Naga dan Saus Buah Naga Pada Perusahaan Kebun Naga Poernama Garut - Neni Dewi Ratnaeni; Dinna Rizky Amelia Putri (Gemawisata: Jurnal Ilmiah Pariwisata, 2025)
This research is motivated by the lack of creativity in samosa processing, the author uses dragon fruit peel filling with the aim of utilizing commonly wasted materials, and introducing to the public that dragon fruit peel can also be processed not only the meat that can be eaten, which of course is no less high nutrition with dragon fruit meat. The method used in this research is research and development, by conducting a series of experiments and development using a secoring scale hedonic test involving 25 panelists. The results of the study determine the standard recipe, namely dragon fruit skin 200 g, chicken 100 g, onion 50 g, paprika 50 g, salt 3 g, flavoring 2 g, curry powder 5 g. The results of the main test calculation of the organoleptic test of Samosa filled with dragon fruit skin and dragon fruit sauce have an average value of 88.8%. . The results of the calculation of business analysis of samosa filled with dragon fruit peel and dragon fruit sauce are Cost of goods per portion of Rp 9,760, Total variable cost of Rp 10,340 Selling price per portion of Rp 25,000, Fixed cost of Rp 1,625,000, BEP 111 units / month, Target Operating income of Rp 4,000,000 will be achieved if sales reach 111 servings / month or with sales of 13 servings / day. Suggestions in this study, namely, in the drying process it is recommended until the water content in the dragon fruit skin comes out a lot so that when cooking it is not watery.